"Khamsa" is the Wealth of our Spirituality - Khalilov Islomjon Dilshodbek ogli; Mukhtorov Kenja Vafo ogli; Abdurakhimov Iskandar Nodirjon ogli; Nabijonov Khurshidbek G'ayratjon ogli (Periodica Journal, 2022)
In this article, we have discussed the great wealth of our grandfather Alisher Navoi, his books. It was about our grandfather's youth and what he did. Information is given about the deeds of our ancestor, the books he wrote and the poems he wrote.
Keywords: Alisher Navoi; Hamsa; Mantiq ut-tayr; Education